1982
DOI: 10.1001/jama.248.21.2864
|View full text |Cite
|
Sign up to set email alerts
|

Sulindac. A potentially renal-sparing nonsteroidal anti-inflammatory drug

Abstract: Three patients experienced rapidly reversible azotemia related to the use of naproxen or ibuprofen but tolerated full-dose sulindac. This article discusses renal toxicity of nonsteroidal anti-inflammatory drugs (NSAIDs), with emphasis on the role of inhibition of prostaglandin synthesis, and reviews evidence supporting a renal-sparing property of sulindac. The current literature assumes that all NSAIDs possess a similar potential for renal toxicity. The data presented suggest that sulindac has less potential f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0
1

Year Published

1983
1983
1998
1998

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(25 citation statements)
references
References 17 publications
0
24
0
1
Order By: Relevance
“…Sulindac was studied because of the suggested lack of inhibition of renal pros taglandins in comparison to other NSAIDs such as indomethacin and ibuprofen [16][17][18][19]. Our results suggest that, in healthy males on a normal sodium diet, the natriuretic response to intravenous furosemide was not inhibited by either ibuprofen or sulindac, while both agents significantly suppressed the stimulation of plasma renin activity.…”
mentioning
confidence: 70%
“…Sulindac was studied because of the suggested lack of inhibition of renal pros taglandins in comparison to other NSAIDs such as indomethacin and ibuprofen [16][17][18][19]. Our results suggest that, in healthy males on a normal sodium diet, the natriuretic response to intravenous furosemide was not inhibited by either ibuprofen or sulindac, while both agents significantly suppressed the stimulation of plasma renin activity.…”
mentioning
confidence: 70%
“…Ciabattoni et al (1980) have first reported that sulindac may be unique because it does not inhibit renal PG synthesis in normal volunteers and in a patient with Bartter's syndrome as measured by urinary PG excretion. These observations were later confirmed by several studies in normal subjects and in patients with chronic glomerular disease or hypertension (Bunning and Barth 1982;Salvetti et al 1982; Ciabattoni et al 1984; Sedor et al 1984; Puddey et al 1985; Vriesendorp et al 1986a). Recently, however, there are controversial results indicating that sulindac reduces urinary excretion of PGE2 and is not specifically renalsparing both in experimental animals and in healthy subjects or in patients with renal, liver of cardiac diseases (Berg and Talseth 1985;Brater et al 1985; Olanoff et al 1985; Roberts et al 1985;Laf et al 1986).…”
mentioning
confidence: 70%
“…The result indicates that sulindac as well as diclofenac sodium does not interfere with BP control obtained by nifedipine, despite of reduced renal PGEZ synthesis. On the other hand, sulindac has been shown to be a renal sparing drug (Bunning and Barth 1982 ;Sedor et al 1984 ;Ciabattoni et al 1984). The rare adverse effect of sulindac on renal function is due to less inhibition of renal PG synthesis, although the inhibitory effect of sulindac on renal PG synthesis is still controversial (Patrono and Dunn 1987; Stillman and Schlesinger 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, more careful evaluation about the effect of NSAIDs on BP control is required. On the other hand, sulindac is shown to have a rare side effect on renal function (Bunning and Barth 1982;Ciabattoni et al 1984;Sedor et al 1984). It may also be probable that sulindac has no adverse affect on hypertension treatment that favors renal function.…”
mentioning
confidence: 99%